Optimalisasi YouTube sebagai Media Dakwah Kreatif di Era Digital - Abdul Rahman Rasyid; Irma Yusriani Simamora (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of digital technology has encouraged the transformation of da’wah from conventional media to digital platforms, one of which is YouTube. YouTube functions not only as an entertainment medium but also as a strategic platform for delivering creative and innovative da’wah messages. This study aims to analyze the optimization of YouTube as a creative da’wah medium in the digital era. This research employs a qualitative approach using content analysis techniques on several Islamic da’wah YouTube channels. The results indicate that optimizing YouTube for creative da’wah can be achieved through attractive content packaging, communicative language, creative use of visual and audio elements, and consistency in conveying Islamic messages. Furthermore, understanding audience characteristics and YouTube’s algorithm plays a crucial role in enhancing the reach and effectiveness of da’wah. This study is expected to contribute academically and serve as a practical reference for preachers and da’wah content creators in developing relevant digital da’wah.